L’émigration Clandestine au Miroir de L’art Audio-Visuel Tunisien: L’image de la Harga Vers Lampedusa Une Tragédie Artistique ou Une Catastrophe Humaine? - Naima, Elfekih (جامعة باجي مختار عنابة - مخبر تحليل العمل والدراسات الأرغونومية, 2017)
This article opens on a contemporary period marked by the increase in illegal immigration accompagnied many catastrophes at sea which have been the subject of extensive media coverage, and by advanced in research on migration. We set up a new avenue of research “Illegal emigration to the mirror of the Tunisian audio-visual art:" The image of Harga to Lampedusa: an artistic tragedy or human catastrophe" has a contemporary look on the representation of illegal immigration in the Tunisian audio-visual art, one aspect until our days abandoned by the research in this area. Our objective is to discover how with whom the audio-visual art represent, talk and shows the Harga from a corpus consisting of a television documentary filmed "Lampedusa, the boat catastrophe ", broadcast by National chain 1, September 18th, 2012, and other artistic creations opening on a new voice of reflection, that will allow us to propose a wider perspective of the problem. Our analytical research shows that the audio-visual art even if it gives a pessimistic view on the Harga, it helps the public to become aware of its gravity. The new insight provided by the audio-visual art on migration never hides treatment with awkwardness the drama of haragas which appears so big that the Tunisian artistic creations found in this theme an easy source of inspiration for dramatic stories without a real critical vision wich treats Harga as a human catastrophe need real solutions. This work is the opportunity to offer some recommendations helping the Tunisian audio-visual art for acting of efficient way with the migration issue which still must win the media field without mishaps.
Keywords: الهجرة غير الشرعية -- الفن السمعي البصري -- الإبداع الفني